1987
DOI: 10.1111/j.1469-8137.1987.tb04883.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF LIGHT ON THE RELATIONSHIP BETWEEN APHIS FABAE SCOP. AND ITS HOST PLANT, VICIA FABA L.

Abstract: SUMMARYPlants of Viciafaba were grown in pots at photosynthetic photon flux densities (PPFD) of 143, 315 or 906 fimo\ m'^ s~^ for 8, 13 or 18 d. The effects of the dry matter loss caused by the feeding of Aphis fabae, or by removal of the cotyledons, were measured. Differences in dry weight between infested and control plants were positively correlated with the dry matter ingested, and increased with PPFD and time. Dry weights of aphid colonies increased non-linearly, but the honeydew produced per unit weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…These interactions were primarily in gaps at both the community and focal plant level. The high light conditions and higher young leaf densities in gaps would allow high exudate production by homopteran herbivores (Garsed et al 1987), which would support mutualistic interactions with ants. These ant interactions may have contributed to the higher predation rates measured on artificial caterpillars in gaps.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions were primarily in gaps at both the community and focal plant level. The high light conditions and higher young leaf densities in gaps would allow high exudate production by homopteran herbivores (Garsed et al 1987), which would support mutualistic interactions with ants. These ant interactions may have contributed to the higher predation rates measured on artificial caterpillars in gaps.…”
Section: Discussionmentioning
confidence: 99%
“…The light treatments are extremes at the ' high' and ' low' ends of the range of PPFD normally experienced by plants and extend the range studied in the previous work (Garsed et al, 1987). The temperatures are in a range considered favourable for aphid growth and in which responses of individuals and populations are well documented (Tsitsipis & Mittler, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the energy retained by the aphids (P) to that consumed (C) shows that light has a strong influence on the use of the energy ingested by the aphids. The values from Table 1 were also used in Figure 3 of Garsed et al (1987), which showed a very strong relationship between the ratio P:C and log PPFD. …”
Section: Growth Analysismentioning
confidence: 99%
See 2 more Smart Citations